The Legal Position of the Use of Blockchain Technology on the Validity of Stamp Duty in the Digital Age - Ariani, Relys Sandi; Setia Negara, Tunggul Anshari; Masykur, Mohammad Hamidi (Institut Agama Islam Negeri Curup, 2024)
The integration of blockchain technology in stamp duty administration requires a clear legal framework to ensure effective implementation. This study evaluates the benefits and challenges of using blockchain in stamp duty imposition and provides regulatory framework recommendations. Using a normative legal approach and analysis of relevant legislation, the research shows that blockchain can significantly enhance efficiency, transparency, and security in the stamp duty process. The immutable nature of blockchain records ensures data integrity and reduces the risk of fraud. Moreover, smart contracts can automate and streamline the transaction process, minimizing human error. However, the adoption of blockchain faces challenges such as high initial costs and the need for regulatory adjustments. In conclusion, the adoption of blockchain in stamp duty administration necessitates comprehensive regulations to ensure the legality and validity of recorded transactions, providing a robust and reliable tax system for the digital age.